Early Modern Civil Discourses
X, 206 p.
Keywords: This collection explores the concept of civility in the early modern period. It addresses a range of writings in English and Scots - among them, conduct manuals, colonial tracts, diaries, letters, dialogues, poetry, drama, chronicles - by English, Welsh and Scots men and women in and about the Atlantic archipelago. It explores the many meanings of civility in the early modern period; it recovers some of the lost associations of civility as well as the complex use of the adjectives 'civil' and 'barbarous' in cultural and colonial encounters.